Medial Septal Area Vasopressin Receptor Subtypes in the Regulation of Urine and Sodium Excretion in Rats - de Arruda Camargo, G. M. P. [UNESP]; de Arruda Camargo, L. A. [UNESP]; Saad, W. A. (Wiley-Blackwell Publishing, Inc, 2009)
The present study aimed to determine the effects of selective antagonists of V(1a), V(2), and V(1a)/V(2) (Conivaptan; Astellas Pharma Inc., Tokyo, Japan) arginine vasopressin (AVP) receptors on the flow of urine and sodium excretion induced by AVP, by means of microinjections into the medial septal area (MSA) of the rat brain. Male Holtzman rats had a guide cannula implanted into the dorsal surface of the MSA. Intravenous infusion of hypotonic saline was used to promote urinary flow, which was collected for 4 h. Pretreatment with the V(1a) antagonist decreased, and the V(2) antagonist and Conivaptan (a V(1a)/V(2) antagonist) increased, the urinary flow induced by AVP. Administration of AVP increased sodium excretion. Pretreatment with V(2) or V(1a) antagonists decreased, and Conivaptan abolished, the sodium excretion induced by AVP. These results indicate that the V(1a) and V(2) receptors of the MSA are important in the central regulation of urine and sodium excretion.
Keywords: vasopressin; medial septal area; V(1a) and V(2) receptors; urine excretion; sodium excretion